2001
DOI: 10.5144/0256-4947.2001.196
|View full text |Cite
|
Sign up to set email alerts
|

Problems with Inpatient Drug users in Jeddah

Abstract: Background:To identify problems associated with the treatment of inpatient drug users in Jeddah, and suggest ways of improving the delivery of health care service to these drug users. Subjects and Methods: Three hundred and two subjects with substance dependence who were admitted to the Voluntary Detoxification Unit of Al Amal Hospital, Jeddah, between January and April 1997 (inclusive) were studied. A data gathering form was designed to collect relevant information. Outcome was recorded after discharge or tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…There was an increase in frequency of amphetamine and cannabis use and decrease of heroin and volatile substance use in the Western region (Osman, 1992(Osman, , 2005Iqbal, 2000Iqbal, , 2001Bassiony, 2008) and in the Eastern region (AbuMadani et al, 2008) over the last two decades. The contradictory findings between Western and Eastern regions could reflect different drug and substance availability and affordability.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There was an increase in frequency of amphetamine and cannabis use and decrease of heroin and volatile substance use in the Western region (Osman, 1992(Osman, , 2005Iqbal, 2000Iqbal, , 2001Bassiony, 2008) and in the Eastern region (AbuMadani et al, 2008) over the last two decades. The contradictory findings between Western and Eastern regions could reflect different drug and substance availability and affordability.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies found that, among substance abuse patients in Saudi Arabia, the prevalence of alcohol abuse ranged from 9% to 70.3% (Osman, A., 1992;Qureshi, 1992 1995; Al-Naheda, 1999;Iqbal, 2000Iqbal, , 2001Qureshi & Al-Habeeb, 2000;Osman, O., 2005;Bassiony, 2008). In Al-Qassim (Central region), alcohol was the most commonly abused substance among substance abuse patients (Qureshi & Al-Habeeb, 2000).…”
Section: Prevalence Of Substance Abusementioning
confidence: 99%
See 3 more Smart Citations